A simulation of film cooling in the leading edge region of a turbine blade (trench effect on film effectiveness from cylinder in crossflow) - Pairan, Mohamad Rasidi (2012)
Film cooling is one of the cooling system techniques applied to the turbine blade. Gas turbine use film cooling technique to protect turbine blade from expose directly to a hot gas to avoid the blade from defect. The focus of this investigation is to investigate the effect of embedded three difference depth of trench at cooling holes geometry to the film cooling effectiveness. Comparisons are made under blowing ratio 1.0, 1.25, 1.5 and 2.0. Three configuration leading edge with depth Case A (0.0125D), Case B (0.0350D) and Case C (0.713D) were compared to leading edge without trench. Result shows that as blowing ratio increased from 1.0 to 1.25, the film cooling effectiveness is increase for leading edge without trench and also for all cases. However when the blowing ratio is increase to 1.5, film cooling effectiveness is decrease for all cases. Meanwhile for blowing ratio 2.0, the result shows the effect of depth is too small for all the cases. Overall the Case B with blowing ratio 1.25 has the best film cooling effectiveness with significant improvement compared to leading edge without trench and with trench Case A and Case C.